The Rise of the Private: Shanghai’s Transforming Housing Typologies - Neeraj Bhatia (Footprint)
‘On top of the sea’ is the literal translation of Shanghai, whose urban structure was built around thin canals that crossed the city. These canals, just as the traditional street in Chinese culture, were able to move people and goods while creating a public arena for interaction. It was infrastructure – streets and canals – that was the basis for the city’s morphology. As the rivers and streets eventually grew, merged, and monumentalised, they created separation. Thus, infrastructure, which once was used to collect, now divided – as is witnessed in the new six-(or more) lane-streets or the Huangpu River, isolating Puxi from Pudong. This transforming notion of infrastructure is directly linked to changes in Shanghai’s housing typologies. The traditional lilong housing structure is comprised of a unit that multiplies through group linkages to create streets. In these lilong dwellings, the street and the architectural type are one. More recently, an influx of high-rise apartment typologies has dislocated the relationship between infrastructure and building. Here, infrastructure is used to subdivide massive plots onto which built form is whimsically placed. The disconnection and monumentalisation of infrastructure that corresponds to these shifting building typologies reveals an even deeper transformation of the public sphere – one in which isolation and alienation are substituting a loss of reality. It is here that we witness the rise of the Private and the emerging loss of public life.